Solve: StartAbsoluteValue StartFraction x Over 6 EndFraction minus StartFraction 7 Over 12 EndFraction EndAbsoluteValue equals StartFraction 11 Over 6 EndFraction. =

Negative Direction:

– 3 lines of math labeled Positive Direction. The first line is: StartFraction x Over 6 EndFraction minus StartFraction 7 Over 12 EndFraction equals negative StartFraction 11 Over 6 EndFraction. The second line is: StartFraction x Over 6 EndFraction equals StartFraction 29 Over 12 EndFraction = –

= –2 lines of math labeled Negative Direction. The first line is: StartFraction x Over 6 EndFraction minus StartFraction 7 Over 12 EndFraction equals negative StartFraction 11 Over 6 EndFraction. The second line is: StartFraction x Over 6 EndFraction equals negative StartFraction 15 Over 12 EndFraction

Positive Direction:

– =

=



Determine the values for x by completing the steps shown.

x = x equals StartFraction 29 Over 2 EndFraction or x equals negative StartFraction 15 Over 2 EndFraction or x = –
x = –x equals negative StartFraction 29 Over 2 EndFraction or x equals StartFraction 15 Over 2 EndFraction or x =
x = –x equals negative StartFraction 29 Over 2 EndFraction or x equals negative StartFraction 15 Over 2 EndFraction or x = –
x = x equals StartFraction 29 Over 2 EndFraction or x equals StartFraction 15 Over 2 EndFraction or x =

1 answer

To solve the equation

\[ \left| \frac{x}{6} - \frac{7}{12} \right| = \frac{11}{6}, \]

we break it down into two cases considering the definition of absolute value.

Positive Direction

  1. Case 1:

\[ \frac{x}{6} - \frac{7}{12} = \frac{11}{6} \]

To solve for \( x \):

\[ \frac{x}{6} = \frac{11}{6} + \frac{7}{12} \]

First, we need a common denominator to add the fractions. The least common multiple of 6 and 12 is 12.

Convert \(\frac{11}{6}\) to have a denominator of 12:

\[ \frac{11}{6} = \frac{22}{12} \]

Now add:

\[ \frac{x}{6} = \frac{22}{12} + \frac{7}{12} = \frac{29}{12} \]

Now, multiply both sides by 6:

\[ x = 6 \cdot \frac{29}{12} = \frac{174}{12} = \frac{29}{2} \]

Negative Direction

  1. Case 2:

\[ \frac{x}{6} - \frac{7}{12} = -\frac{11}{6} \]

To solve for \( x \):

\[ \frac{x}{6} = -\frac{11}{6} + \frac{7}{12} \]

Again, convert \(-\frac{11}{6}\) to have a denominator of 12:

\[ -\frac{11}{6} = -\frac{22}{12} \]

Now add:

\[ \frac{x}{6} = -\frac{22}{12} + \frac{7}{12} = -\frac{15}{12} \]

Now, multiply both sides by 6:

\[ x = 6 \cdot -\frac{15}{12} = -\frac{90}{12} = -\frac{15}{2} \]

Solution:

Thus, the solutions for \( x \) are:

\[ x = \frac{29}{2} \quad \text{and} \quad x = -\frac{15}{2} \]

Final answer presentation:

  • \( x = \frac{29}{2} \)
  • \( x = -\frac{15}{2} \)